Profil Kecerdasan Emosional Peserta Didik SMK Negeri 2 Padang - Sulis Rezki Anggraini; Helma Helma; Citra Imelda Usman (Islamic Counseling: Jurnal Bimbingan dan Konseling Islam, 2023)
The background of this research is that there are students who cannot control anger or resentment uttered by their peers, students who do not have confidence before starting a presentation in front of the class, and who lose control when they are angry with their peers. The purpose of this study was to describe the profile of the emotional intelligence of students in class XI Marketing at SMK Negeri 2 Padang from the aspects of: 1) Recognizing emotions 2) Managing emotions 3) Motivating yourself 4) Empathy 5) Building Relationships. This research was conducted using a quantitative descriptive method. The research population was 96 students who were selected by total sampling technique. The instrument used is a questionnaire. As for data analysis using percentages. Based on the results of research on the emotional intelligence profile of students in class XI Marketing at SMK Negeri 2 Padang of: 1) Recognizing emotions is in a fairly high category and in high caligniting in other aspect of emocional intelligence in this study. Based on the results of this study, it is recommended for counselor to make a model to increasing their emotional intelligence.quite high, and for future researchers to create an effective model guidance and couselerto improve students' emotional intelligence.